2017
DOI: 10.1016/j.actbio.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Triggered Resolvin D1-modified materials promote the accumulation of pro-regenerative immune cell subsets and enhance vascular remodeling

Abstract: Many goals in tissue engineering rely on modulating cellular localization and polarization of cell signaling, including the inhibition of inflammatory infiltrate, facilitation of inflammatory cell egress, and clearance of apoptotic cells. Omega-3 polyunsaturated fatty acid-derived resolvins are gaining increasing recognition for their essential roles in inhibition of neutrophil invasion into inflamed tissue and promotion of macrophage phagocytosis of cellular debris as well as their egress to the lymphatics. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 91 publications
0
42
0
Order By: Relevance
“…In a recent report, AT-RvD1 was detected by liquid chromatography–tandem mass spectrometry (LC-MS/MS)-based metabololipidomics in human plasma from patients affected by coronary heart disease treated with aspirin with and without an EPA and DHA supplement [26]. AT-RvD1 released from a bio-degradable material has been recently shown to decrease neutrophil infiltration and to increase the anti-inflammatory monocyte/macrophage population in a murine model [38]. In another recent study, AT-RvD1 has been shown to suppress TGF-β-induced migration and invasion of A549 lung cancer cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, AT-RvD1 was detected by liquid chromatography–tandem mass spectrometry (LC-MS/MS)-based metabololipidomics in human plasma from patients affected by coronary heart disease treated with aspirin with and without an EPA and DHA supplement [26]. AT-RvD1 released from a bio-degradable material has been recently shown to decrease neutrophil infiltration and to increase the anti-inflammatory monocyte/macrophage population in a murine model [38]. In another recent study, AT-RvD1 has been shown to suppress TGF-β-induced migration and invasion of A549 lung cancer cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Because these typically “pro-regenerative” MP subpopulations predominate the SS as early as day 7, increasing their recruitment may offer only modest therapeutic efficacy for muscle degeneration, which occurs over weeks. A more promising strategy may be to bias recruited cells toward pro-regenerative cytokine secretion using appropriately engineered delivery of immune modulatory molecules[44], [49], [50]. …”
Section: Discussionmentioning
confidence: 99%
“…The device eluted biologically active RvD1 for more than 3 weeks in vitro. A similar approach was taken by Sok et al in loading AT-RvD1 into PLGA scaffolds implanted under mouse skin (Sok, Tria et al 2017). Sustained release of SPM (e.g.…”
Section: Translation: Resolution Pharmacology In Vascular Injurymentioning
confidence: 98%